From Resistance to Transformation: A Generic Metric of Resilience Through Viability - Béné, Christophe; Doyen, Luc (Wiley, 2018)
In the last two decades resilience has emerged as a promising concept that can help societies and more generally social‐ecological systems become less vulnerable to shocks and stressors. As such it has been adopted by a large number of disciplines—from psychology, physics, and ecology to disaster risk reduction, climate change adaption, and humanitarian and food security interventions. However, although numerous definitions or measures of resilience have been proposed, those were mainly discipline centered and, as such, failed to provide an adequate overarching framework. This paper explores the question of the formalization and measurement of resilience, with the objective to develop a generic metric that applies across the disciplines and to the different interpretations of resilience. Building on the definitions found in the literature, a continuum of five categories of resilience responses is identified: (i) resistance, (ii) coping strategies, (iii) adaptation, (iv) adaptive preference, and (v) transformation. Those categories are then reframed into a generic metric, using viability analysis—a mathematical formalism which builds on dynamic systems and control theory. Theoretical and empirical analyses are then conducted, looking in particular at how inertia and costs associated with the types of responses influence the level of resilience. To illustrate this new metric, we draw on two models widely discussed in the resilience literature: the exploitation of renewable resources and the case of lake eutrophication. Both theoretical and numerical analyses demonstrate the relevance of the typology as a generic framework for resilience but also highlight transformation as a particular case of resilience response.